Cascade-penetrating domino-ferroptosis nano inducer synergizes with sonodynamic therapy for anaplastic thyroid cancer - Peng Dong; Yun-Bo Chi; Deng-Ke Teng; Yuan-Qiang Lin; Ling-Yu Zhu; He-Qun Li; Jia-Yu Yang; Jia-Rui Du; Zong-Tao Zhang; Hai-Tao Ran; Guo-Qing Sui; Hui Wang; et al. (Materials Today Bio)
Ferroptosis, an iron-dependent, nonapoptotic form of regulated cell death, has become a new approach for antitumor treatment. However, the insufficient accumulation and poor penetration of ferroptosis inducers deep in tumors greatly limit their therapeutic effects. In this study, we constructed a cascade penetrating metal‒polyphenol ultrasonic molecular probe, Fe3+Cur-PFP@IR780-LIP (FCIPL). The nanoparticles (NPs) can penetrate deep into tumors in a stepwise fashion via specific targeting combined with cavitation effects resulting from acoustic droplet vaporization (ADV) and ultrasound-targeted microbubble destruction (UTMD) technology. Then, the drug can be successfully delivered into the mitochondria of tumor cells under the cascade response of ultrasound and the tumor microenvironment, inducing the ferroptosis domino cascade. The nanoparticles disassemble, releasing the Fenton reaction catalyst Fe2+ and the ferroptosis inducer Cur, which together constitute the ferroptosis ''amplifier,'' promoting the domino-like burst of lipid peroxide (LPO) and triggering ferroptosis. Simultaneously, the sonosensitizer IR780 is activated to induce sonodynamic therapy (SDT). Under the synergistic action of ferroptosis and SDT, a waterfall-like therapeutic effect is produced. In terms of diagnosis, this nanoplatform combines multimodal (ultrasound, photoacoustic, magnetic resonance and fluorescence) imaging to improve the diagnostic performance of anaplastic thyroid cancer (ATC) and provide a visualization strategy for early diagnosis. In this study, the advantages of ultrasound technology are exploited to achieve deep penetration of drugs and overcome the limitations of a single treatment modality, achieve optimal diagnostic and treatment effects, and provide new ideas for integrating ATC diagnosis and treatment.